2015
DOI: 10.1124/dmd.115.066316
|View full text |Cite
|
Sign up to set email alerts
|

Dose of Phenobarbital and Age of Treatment at Early Life are Two Key Factors for the Persistent Induction of Cytochrome P450 Enzymes in Adult Mouse Liver

Abstract: Drug treatment of neonates and infants and its long-term consequences on drug responses have emerged in recent years as a major challenge for health care professionals. In the current study, we use phenobarbital as a model drug and mouse as an in vivo model to demonstrate that the dose of phenobarbital and age of treatment are two key factors for the persistent induction of gene expression and consequential increases of enzyme activities of Cyp2b, Cyp2c, and Cyp3a in adult livers. We show that phenobarbital tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 44 publications
(55 reference statements)
3
28
0
Order By: Relevance
“…In our own study, mice treated with less than 100 mg/kg of phenobarbital at the neonatal age do not display persistent induction of CYP2B10, CYP2C29, or CYP3A11 through adult life. Only neonatal mice that were administered a dose of phenobarbital greater than this exhibited the persistent elevation of these P450 enzymes in their livers throughout life [35]. Our study also demonstrated that age is another key factor for persistent induction of P450 expression in adult mouse liver.…”
Section: Neonatal Exposure To Xenobiotics Alters P450 Expression and supporting
confidence: 53%
See 2 more Smart Citations
“…In our own study, mice treated with less than 100 mg/kg of phenobarbital at the neonatal age do not display persistent induction of CYP2B10, CYP2C29, or CYP3A11 through adult life. Only neonatal mice that were administered a dose of phenobarbital greater than this exhibited the persistent elevation of these P450 enzymes in their livers throughout life [35]. Our study also demonstrated that age is another key factor for persistent induction of P450 expression in adult mouse liver.…”
Section: Neonatal Exposure To Xenobiotics Alters P450 Expression and supporting
confidence: 53%
“…Adult male rats treated with diethylstilbestrol, a synthetic estrogen, at the neonatal age showed significant elevation in specifically CYP2C6 hepatic protein level, while rats administered phenobarbital show specific increases in CYP2C7 and CYP2B hepatic protein levels, indicating these drugs have the ability to alter the expression of certain P450 isoforms, rather than drug metabolism activity as a whole [28–30]. Phenobarbital has been the most commonly utilized drug to observe this phenomenon, and the persistent induction of CYP3A, 2B, 2C in rats and mice following early life exposure has been demonstrated numerous times [27, 28, 30–35]. Neonatal administration of lindane, an organochlorine used for lice treatment, to rats also produced an increase in the expression of CYP2B protein, along with CYP1A, later in life [36], indicating different compounds may set certain P450 levels through similar mechanisms early in life.…”
Section: Neonatal Exposure To Xenobiotics Alters P450 Expression and mentioning
confidence: 99%
See 1 more Smart Citation
“…In this talk, we reported that the dose of drug and age of treatment in early life are two key factors for the persistent induction of gene expression and consequent increases of enzyme activities of several P450 genes in Cyp2b, Cyp2c, and Cyp3a subfamilies in adult mouse liver (Tien et al, 2015). When mice mature under normal conditions (no drug treatment in early life), their P450 expression follows the typical ontogenic pattern with increased expression with age (Peng et al, 2012).…”
Section: Effects Of Drug Treatment At Early Life On Interindividualmentioning
confidence: 99%
“…Recombinant human CYPs and human liver microsomes (HLM) were purchased from XenoTech (Lenexa, KS). Mouse liver microsomes (MLM) were prepared from the liver of wild-type and Cyp3a-null mice according to the previously established methods (13). Methoxylamine and NADPH were purchased from Sigma-Aldrich (St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%